Occluding junctions as novel regulators of tissue mechanics during wound repair - Carvalho, Lara (2022)
This research was supported by Fundação para a Ciência e a Tecnologia (SFRH/BPD/84569/2012 to L. Carvalho, PD/ BD/106058/2015 to S. Ponte, SFRH/BD/119240/2016 to A.S. Nunes, UID/FIS/00618/2013, PTDC/FIS-MAC/28146/2017, PTDC/ BIA-BID/29709/2017 and CONGENTO), the European Research Council (2007-StG-208631 and ERC-2015-PoC-713735-EMODI), a European Commission Marie Curie Intra-European Fellowship (PIEF-GA-2009-255573), the Partenariat Hubert Curien Pessoa program (30920XM), the European Science Foundation (Quantitative Models of Cellular and Developmental Biology Research Networking Program, grant 6839), and the iNOVA4Health Research Unit (UID/Multi/04462/2013), cofunded by Fundação para a Ciência e Tecnologia, through national funds and by FED ER under the PT2020 Partnership Agreement.